Resin composition, adhesive film and printed circuit board containing the same

By using polyarylethernitrile toughening agent containing reactive side groups in the adhesive film, the problem of deterioration of toughness caused by high-filled inorganic fillers is solved, and the comprehensive performance improvement of high Tg, high copper foil peel strength and moisture and heat resistance is achieved. It is suitable for thin circuit applications of printed circuit boards.

CN115819926BActive Publication Date: 2025-03-04GUANGDONG SHENGYI SCI TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211622521.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2025-03-04
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

After adding high-filled inorganic filler, the toughness of the existing adhesive films becomes poor, making it difficult to meet the requirements of high Tg, high peel strength of copper foil and moisture and heat resistance.

Method used

A polyarylethernitrile toughening agent containing reactive side groups is used to combine an appropriate amount of resin and filler to form a resin composition, and the toughness and resistance of the adhesive film are improved through crosslinking reaction.

Benefits of technology

It significantly improves the toughness of the adhesive film, while maintaining high Tg, copper foil peel strength and PCT resistance. It is suitable for printed circuit boards with multi-layer laminated plates, especially for thin circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004002638360000121
    Figure BDA0004002638360000121
  • Figure BDA0004002638360000122
    Figure BDA0004002638360000122
Patent Text Reader

Abstract

The present invention provides a resin composition, and an adhesive film and a printed circuit board containing the same. The resin composition comprises the following components in parts by weight: 25-70 parts of resin, 30-60 parts of filler, and 1-20 parts of polyarylethernitrile containing reactive side groups. In the present invention, a polyarylethernitrile toughening agent containing reactive side groups is selected, so that the adhesive film and the resin-coated copper foil prepared by the resin composition can well solve the problem of poor toughness caused by the addition of high-filled inorganic fillers, have good toughness, and can also have the characteristics of high Tg, high copper foil peeling strength, PCT resistance, etc., and can be applied to printed circuit boards of multi-layer laminates, especially printed circuit boards of multi-layer laminates for making fine circuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin adhesive films and relates to a resin composition and an adhesive film and a printed circuit board containing the same. Background Art

[0002] As electronic information products are mainly oriented towards the design trend of being light, thin, short and multifunctional in the future, the printed circuit substrate, as the main support for electronic components, is also constantly improving its technical level to provide high-density wiring, thin shape, fine aperture, multi-dimensional, etc. The substrate material determines the performance of the printed circuit substrate to a large extent, so it is urgent to develop a new generation of base materials.

[0003] Adhesive films or resin-coated copper foils without reinforcement materials are being developed and applied as a new generation of matrix materials because they can achieve thinner shapes, high-density wiring, fine pores, and multi-dimensional stereoscopic molding. Since there are no reinforcement materials, high-filled inorganic fillers are generally added to improve the thermal expansion coefficient, chemical resistance, mechanical strength, etc. of the adhesive film material. However, it is precisely because of the introduction of high-filled inorganic fillers that the toughness of the adhesive film deteriorates. In order to compensate for the toughness, toughening agents such as rubber are usually added for toughening. However, the newly introduced toughening agents will deteriorate other properties. How to improve the toughness of the adhesive film without reducing other properties, such as Tg, moisture and heat resistance, etc., is the focus of research in this field.

[0004] Therefore, in the art, it is desired to develop a material for fine circuits that can improve the toughness of the film by adding a high-filling filler, and at the same time has a high Tg, a high copper foil peel strength, and good moisture and heat resistance. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a resin composition, and an adhesive film and a printed circuit board containing the same.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides a resin composition, comprising the following components in parts by weight:

[0008] Resin 25-70 parts

[0009] Filler 30-60 parts

[0010] 1-20 parts of polyarylethernitrile toughening agent containing reactive side groups.

[0011] In the present invention, a polyarylethernitrile toughening agent containing reactive side groups is selected, so that the adhesive film and the resin-coated copper foil prepared from the resin composition can well solve the problem of poor toughness caused by the addition of high-filled inorganic fillers, have good toughness, and can also have the characteristics of high Tg, high copper foil peeling strength, PCT resistance, etc., and can be applied to printed circuit boards of multi-layer laminated boards, especially printed circuit boards of multi-layer laminated boards with fine circuits.

[0012] In the present invention, the content of resin in the resin composition is 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts, 60 parts, 65 parts, 68 parts or 70 parts.

[0013] In the present invention, the content of filler in the resin composition is 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts or 60 parts.

[0014] In the present invention, the content of the poly(arylene ether nitrile) toughening agent containing reactive side groups is 1 part, 2 parts, 3 parts, 5 parts, 7 parts, 10 parts, 13 parts, 15 parts, 18 parts or 20 parts.

[0015] In the present invention, the "parts" and "parts by weight" involved are all calculated based on solid content and do not include solvents, dispersants, etc.

[0016] Preferably, the reactive side groups include any one of epoxy, hydroxyl, carboxyl or amine or a combination of at least two. The polyarylether nitrile toughening agent containing reactive side groups in the present invention contains side groups such as epoxy, hydroxyl, carboxyl or amine, and the reactive side groups can cross-link with the resin and / or curing agent in the resin composition to increase the cross-linking density of the reaction, so that the prepared adhesive film has good toughness, high Tg, and high copper foil peeling strength, and can also improve the PCT resistance of the adhesive film. Preferably, the content range of the reactive side groups can be 10-500μeq / g, such as 10μeq / g, 20μeq / g, 50μeq / g, 80μeq / g, 100μeq / g, 150μeq / g, 200μeq / g, 250μeq / g, 300μeq / g, 350μeq / g, 400μeq / g, 450μeq / g or 500μeq / g, etc.

[0017] Preferably, the number average molecular weight of the poly(arylene ether nitrile) containing reactive side groups is 20,000-200,000, for example, 20,000, 30,000, 50,000, 80,000, 100,000, 130,000, 150,000, 180,000 or 200,000, and the number average molecular weight is measured by gel permeation chromatography based on polystyrene calibration according to GB / T 21863-2008.

[0018] Preferably, the resin is any one of epoxy resin, phenolic resin, cyanate ester, polyphenylene ether, maleimide resin, hydrocarbon resin, acrylate resin, polyimide resin, silicone resin, polyester resin or polystyrene, or a combination of at least two thereof.

[0019] Preferably, the epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.

[0020] Preferably, the filler is an inorganic filler.

[0021] Preferably, the filler is a silica filler, preferably spherical silica.

[0022] Preferably, the resin composition further comprises a curing agent, and the curing agent comprises any one of phenolic resin and active ester or a combination of both.

[0023] Preferably, the phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.

[0024] In the present invention, when the main resin contains epoxy resin, its curing agent can be phenolic resin, active ester, etc., while mercaptan or amine curing agents (such as dicyandiamide or aromatic amine, etc.) are not suitable for use, as such curing agents will cause the PCT resistance of the film to deteriorate after curing. Preferably, the content of the curing agent in the resin composition is 10-30 parts by weight, such as 10 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts or 30 parts.

[0025] In the present invention, a thermoplastic resin may be further added without affecting the comprehensive performance of the resin composition. Examples of the thermoplastic resin include polyvinyl acetal resin, polyamide-imide resin, polyether sulfone resin, polysulfone resin and the like.

[0026] On the other hand, the present invention provides a resin glue solution, which is obtained by dissolving or dispersing the above-mentioned resin composition in a solvent.

[0027] As the solvent in the present invention, there is no particular limitation. As specific examples, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol-methyl ether, carbitol, and butyl carbitol, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethoxyethyl acetate and ethyl acetate, nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be cited. The above solvents can be used alone or in combination of two or more. Preferably, aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene are mixed with ketone fluxes such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The amount of the solvent used can be selected by those skilled in the art according to their own experience so that the obtained resin glue reaches a viscosity suitable for use.

[0028] On the other hand, the present invention provides an adhesive film, which includes a release film, the resin composition as described above attached to the release film after coating and drying, and a protective film covering the resin composition.

[0029] The adhesive film of the present invention, because it contains the resin composition as described above, can have good toughness and can also have the characteristics of high Tg, high copper foil peeling strength, PCT resistance and the like.

[0030] Preferably, the thickness of the adhesive film is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.

[0031] Preferably, after the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm, for example, 6.2 N / cm, 6.5 N / cm, 6.8 N / cm, 7.0 N / cm, 7.2 N / cm, 7.5 N / cm, 7.8 N / cm or 8.0 N / cm.

[0032] On the other hand, the present invention provides a resin-coated copper foil, comprising a copper foil, a resin layer and a protective film coated on the resin layer, wherein the resin layer is the above-mentioned resin composition attached to the copper foil after coating and drying.

[0033] Preferably, the thickness of the resin layer is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.

[0034] Preferably, the copper foil has a thickness of 1-105 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm or 105 μm, preferably 3-35 μm, further preferably 5-18 μm.

[0035] In another aspect, the present invention provides a prepreg, comprising a substrate and the above-mentioned resin composition attached to the substrate by impregnation and drying.

[0036] The semi-cured sheet of the present invention may also be referred to as a prepreg or a bonding sheet, and the substrate of the present invention may also be referred to as a reinforcing material.

[0037] Preferably, the substrate is E-glass fiber cloth, NE-glass fiber cloth, quartz glass fiber cloth or aromatic amine cloth.

[0038] In another aspect, the present invention provides a laminate comprising at least one prepreg as described above.

[0039] In another aspect, the present invention provides a metal foil-clad laminate, comprising one or at least two laminated prepregs as described above, and metal foil located on one side or both sides of the laminated prepregs.

[0040] Preferably, the metal foil is copper foil.

[0041] In another aspect, the present invention provides a printed circuit board, comprising one or at least two laminated prepregs as described above.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] In the present invention, a polyarylethernitrile toughening agent containing reactive side groups is selected, so that the adhesive film and the resin-coated copper foil prepared from the resin composition can well solve the problem of poor toughness caused by the addition of high-filled inorganic fillers, have good toughness, and can also have the characteristics of high Tg, high copper foil peeling strength, PCT resistance, etc., and can be applied to printed circuit boards of multi-layer laminated boards, especially printed circuit boards of multi-layer laminated boards with fine circuits. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Synthesis example 1

[0046] Add diphenolic acid monomer, 2,6-dichlorobenzonitrile monomer, catalyst potassium carbonate, dehydrating agent toluene, and first solvent N-methylpyrrolidone in proportion to a container equipped with a mechanical stirring device, a reflux condensing device, and a nitrogen inlet and outlet, then start the mechanical stirring device and slowly introduce nitrogen into the mixed system; wherein the molar ratio of diphenolic acid monomer, 2,6-dichlorobenzonitrile monomer, and catalyst is 1:1:0.01, and the amount of the three substances is much smaller than the amount of the dehydrating agent and the first solvent, and the dehydrating agent is 1:1:0.01. The mass ratio of the aqueous solution to the bisphenol acid monomer is 25:1; the volume ratio of the dehydrating agent to the first solvent is 1:3; the system temperature is slowly raised to 170°C and maintained for 2 hours. When the reaction system no longer generates water and is taken out of the system, the reaction is continued for 2 hours to ensure that the reaction is fully completed, and then heated and stirred, and the product after the reaction is poured into anhydrous ethanol to precipitate a solid, which is filtered, crushed, washed and dried to obtain a polyarylether nitrile C1 containing a pendant carboxyl group, with a number average molecular weight of 56,000.

[0047] Synthesis example 2

[0048] 4-aminophenyl hydroquinone monomer, 2,6-dichlorobenzonitrile monomer, potassium phosphate catalyst, xylene dehydrating agent, and N,N-dimethylformamide first solvent are added in proportion to a container with a mechanical stirring device, a reflux condensing device, and a nitrogen inlet and outlet, and then the mechanical stirring device is started and nitrogen is slowly introduced into the mixed system; wherein the molar ratio of 4-aminophenyl hydroquinone monomer, 2,6-dichlorobenzonitrile monomer, and catalyst is 1:1:0.02, and the three substances are much smaller than the dehydrating agent and the first solvent The dosage is as follows: the mass ratio of the dehydrating agent to the 4-aminophenyl hydroquinone monomer is 20:1; the volume ratio of the dehydrating agent to the first solvent is 1:2; the system temperature is slowly raised to 160°C and maintained for 3 hours. When the reaction system no longer generates water and is taken out of the system, the reaction is continued for 2 hours to ensure that the reaction is fully completed, and then heated and stirred, and the product after the reaction is poured into deionized water to precipitate a solid, which is filtered, crushed, washed and dried to obtain a polyarylether nitrile C2 containing a pendant amino group with a number average molecular weight of 83,000.

[0049] Example 1

[0050] 40 parts of epoxy resin (HEXION, EPR627) and 19 parts of phenolic resin (Dow Chemical, XZ92741), 40 parts of silica (admatechs, 2050MB), and 1 part of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0051] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0052] Example 2

[0053] 34 parts of epoxy resin (Nippon Kayaku, NC3000H) and 16 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 10 parts of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0054] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0055] Example 3

[0056] 27 parts of epoxy resin (Momentive, EPIKOTE1001) and 13 parts of active ester (Japan DIC, HPC-8000-65T), 40 parts of silica (admatechs, 2050MB), and 20 parts of toughening agent (polyarylether nitrile C2 containing pendant amino groups) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0057] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0058] Example 4

[0059] 20 parts of cyanate (Lonza, BA3000) and 30 parts of maleimide resin (CYTEC, M5250), 40 parts of silica (admatechs, 2050MB), 10 parts of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0060] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0061] Example 5

[0062] 30 parts of polyphenylene ether (SABIC, MX90), 20 parts of hydrocarbon resin (Japan Soda, B3000), 40 parts of silica (admatechs, 2050MB), and 10 parts of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0063] The above solution is coated on the release film, dried, and then placed in a 120℃ oven for 3-5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board are pressed and cured (temperature 100℃, pressure 0.5MPa, time 1min), the release film is torn off, and the surface is treated and copper electroplated to form a laminated printed circuit board with circuits.

[0064] Example 6

[0065] The difference from Example 1 is that the phenolic resin (Dow Chemical, XZ92741) is replaced by an equal weight portion of dicyandiamide (purchased from BASF).

[0066] Comparative Example 1

[0067] 40 parts of epoxy resin (Nippon Kayaku, NC3000H), 20 parts of phenolic resin (HEXION, PHL6635), and 40 parts of silica (admatechs, 2050MB) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0068] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0069] Comparative Example 2

[0070] 39.5 parts of epoxy resin (Nippon Kayaku, NC3000H), 20 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 0.5 parts of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0071] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0072] Comparative Example 3

[0073] 23 parts of epoxy resin (Nippon Kayaku, NC3000H) and 12 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 25 parts of toughening agent (polyarylether nitrile C1 containing pendant carboxyl groups) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0074] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.

[0075] Comparative Example 4

[0076] 34 parts of epoxy resin (Nippon Kayaku, NC3000H), 16 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 10 parts of nitrile rubber (ZEON, Nipol 1072CG) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.

[0077] The above solution is coated on the release film, dried, and then placed in a 120℃ oven for 3-5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board are pressed and cured (temperature 100℃, pressure 0.5MPa, time 1min), the release film is torn off, and the surface is treated and copper electroplated to form a laminated printed circuit board with circuits.

[0078] Comparative Example 5

[0079] The only difference from Example 1 is that the poly(arylene ether nitrile) containing pendant carboxyl groups is replaced by an equal weight portion of poly(arylene ether nitrile) containing no reactive pendant groups (PEN-1100, Sichuan Chemical New Materials).

[0080] Comparative Example 6

[0081] The difference from Example 1 is that the poly(arylether nitrile) C1 containing pendant carboxyl groups is replaced by an equal weight portion of modified polyether ketone (Evonik, 1000P).

[0082] Comparative Example 7

[0083] The difference from Example 1 is that the poly(arylethernitrile) C1 containing pendant carboxyl groups is replaced by an equal weight portion of polyethersulfone (SOLVAY, 3600RP).

[0084] The performance tests of the embodiments and comparative examples were carried out as follows:

[0085] (1) Bending resistance: Tested according to the method specified in JIS C-6471, test conditions 0.5kg / 0.8R;

[0086] (2) Copper foil peel strength: The IPC-TM-650 2.4.9 method is used to test the peel strength of the copper foil layer of the surface copper electroplating;

[0087] (3) Fine line reliability: the percentage of short circuits in the test circuit after reflow soldering. When the percentage is greater than 90%, it is "excellent", when the percentage is less than 80%, it is "poor", and the rest is "good";

[0088] (4) PCT resistance: After curing, the film is placed in a pressure cooker and treated at 121°C and 2 atm for 2 hours. It is then immersed in a tin furnace at 288°C for 5 minutes. No blistering or delamination is recorded as one time. Repeat the immersion in the tin furnace until blistering or delamination occurs. If the number of times is greater than 20, it is considered "excellent", if the number is less than 5, it is considered "poor", and the rest of the times are considered "good".

[0089] (5) Tg (DSC): tested using IPC-TM-650 2.4.25 method.

[0090] The performance tests of the above embodiments and comparative examples are compared in Tables 1 and 2 below.

[0091] Table 1

[0092]

[0093] Table 2

[0094]

[0095] It can be seen from Table 1 and Table 2 that the films of Examples 1-5 have high Tg, good toughness, high copper foil peel strength, excellent PCT resistance, and excellent fine line reliability. Example 6 uses dicyandiamide curing agent to cure epoxy, which makes the film's PCT resistance and fine line reliability worse.

[0096] Comparative Example 1 did not add the polyarylether nitrile toughening agent containing reactive side groups of the present invention, and the toughness was poor, and the copper foil peeling strength was low; the amount of polyarylether nitrile toughening agent containing reactive side groups added in Comparative Example 2 was too little, the toughness was not greatly improved, and the copper foil peeling strength was low; the amount of polyarylether nitrile toughening agent containing reactive side groups added in Comparative Example 3 was too much, resulting in poor PCT resistance. Comparative Example 4 introduced a nitrile rubber toughening agent, resulting in a decrease in Tg and poor PCT resistance. In Comparative Example 5, polyarylether nitrile without side groups was used, and the PCT resistance was general; Comparative Examples 6 and 7 used other types of toughening resins, and the copper foil peeling strength was low, the toughness was poor, and the PCT resistance was poor.

[0097] The applicant declares that the present invention uses the above embodiments to illustrate the resin composition of the present invention and the adhesive film and printed circuit board containing the same, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that The resin composition comprises the following components in parts by weight: Resin 25-70 parts Inorganic filler 40-60 parts 1-20 parts of polyarylethernitrile toughening agent containing reactive side groups; The resin is an epoxy resin, and the resin composition further comprises 10-30 parts by weight of a curing agent; the curing agent comprises any one or a combination of two of a phenolic resin or an active ester; Alternatively, the resin is a combination of at least two of cyanate ester, polyphenylene ether, maleimide resin or hydrocarbon resin; The reactive side groups include any one of epoxy groups, hydroxyl groups, carboxyl groups or amine groups, or a combination of at least two of them.

2. The resin composition according to claim 1, characterized in that The epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.

3. The resin composition according to claim 1, characterized in that The inorganic filler is a silicon dioxide filler.

4. The resin composition according to claim 3, characterized in that The inorganic filler is spherical silica.

5. The resin composition according to claim 1, characterized in that When the resin is a combination of at least two of cyanate ester, polyphenylene ether, maleimide resin or hydrocarbon resin, the resin composition further comprises 10-30 parts by weight of a curing agent, and the curing agent comprises any one or a combination of two of phenolic resin or active ester.

6. The resin composition according to claim 1, characterized in that The phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.

7. A resin glue, characterized in that: The resin composition is obtained by dissolving or dispersing the resin composition as claimed in any one of claims 1 to 6 in a solvent.

8. An adhesive film, characterized in that: The adhesive film comprises a release film, a resin composition according to any one of claims 1 to 6 attached to the release film after coating and drying, and a protective film covering the resin composition.

9. The adhesive film according to claim 8, characterized in that: The thickness of the adhesive film is 5-300 μm.

10. The adhesive film according to claim 9, characterized in that: The thickness of the adhesive film is 10-200 μm.

11. The adhesive film according to claim 10, characterized in that: The thickness of the adhesive film is 20-100 μm.

12. The adhesive film according to claim 8, characterized in that: After the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm.

13. A resin-coated copper foil, characterized in that: The resin-coated copper foil comprises a copper foil, a resin layer and a protective film coated on the resin layer. The resin layer is a resin composition as claimed in any one of claims 1 to 6 attached to the copper foil after coating and drying.

14. The resin-coated copper foil according to claim 13, characterized in that The thickness of the resin layer is 5-300 μm.

15. The resin-coated copper foil according to claim 14, characterized in that The thickness of the resin layer is 10-200 μm.

16. The resin-coated copper foil according to claim 15, characterized in that The thickness of the resin layer is 20-100 μm.

17. The resin-coated copper foil according to claim 13, characterized in that: The copper foil has a thickness of 1-105 μm.

18. A prepreg, characterized in that: The prepreg comprises a substrate and the resin composition according to any one of claims 1 to 6 attached to the substrate after impregnation and drying.

19. A laminated board, characterized in that: The laminate comprises at least one prepreg according to claim 18.

20. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises one or at least two stacked prepregs as claimed in claim 18, and metal foil located on one side or both sides of the stacked prepregs.

21. A printed circuit board, characterized in that: The printed circuit board comprises one or at least two superimposed prepregs according to claim 18.

Citation Information

Patent Citations

  • Polyarylether nitrile / epoxy resin copolymerized modified composition and preparation method and application thereof

    CN104045978A